Digital competencies at work - Oberländer, Maren (2023)
The digitalized work environment poses challenges to the workforce, such as the meaningful use of ever-new technological advances, dealing with increasingly complex tasks, or effective collaboration in dispersed work groups. The individual worker needs to adapt to rapidly increasing demands due to far-reaching changes in the workplace, to complete their everyday work tasks. However, there is an increasing discrepancy between the existing and required digital competencies in the workforce. Due to the urgent need to expand the scientific knowledge on this important topic, the main focus of this dissertation is on the development and measurement of the construct of digital competencies at work. In the scientific literature, a comprehensive framework that integrates the perspectives of prior research and practitioners in a work context has not been developed yet. Additionally, a common definition of digital competencies at work was still lacking although many wordings have been used for the concept. Modern work practices, such as the ubiquity of remote work for office workers emphasize the importance of digital communication and collaboration competencies at work. Yet, to date, there was no measurement tool for individual digital communication and collaboration competencies at work that is needed to conduct more scientific research on the construct. Another research gap derived from the results of the prior studies in this dissertation measuring digital competencies: The high mean values in all collected data sets led to the assumption that office workers might over-estimate their digital competencies. However, the research question of how the self-assessment of workers’ digital communication and collaboration competencies can be influenced by varying instructions has not yet been explored in an experimental study. Moreover, to further explore the nomological net of the construct, the relationship between digital communication and collaboration competencies and the motivation to train those were investigated. In my dissertation, I realized the collection of quantitative and qualitative data in nine samples and conducted a literature review to address the outlined research gaps. By integrating perspectives from research and practice and combining diverse methods, a coherent and detailed framework of digital competencies at work was created and a definition of the concept was provided in Paper 1. As depicted in Paper 2, building on the theoretical framework and prior research, digital communication and collaboration competencies were identified as dimensions with particular relevance to the challenges of today’s work environments. By using mixed methods, a measurement tool for digital communication and collaboration competencies was developed. The role of those competencies as potential resources in a gain spiral with social support, ultimately boosting work engagement in the unique setting of a pandemic that fundamentally altered the way of work worldwide based on the Job Demands-Resource model (Demerouti et al., 2001) and the conservation of resources theory (Hobfoll, 2011) was explored. Although results did not support the assumption of a gain spiral, we found that digital competencies, social support, and work engagement were stable and high during the crisis. The findings add knowledge about the motivational processes of workers in times of crisis. Subsequently, in Paper 3 the initial measurement tool was refined into a reliable and valid short-scale of digital communication and collaboration competencies at work. In several studies, the short-scale was validated and the nomological net of the constructs was explored. The last part of my dissertation is dedicated to the systematic examination of the effect that varying instructions have on workers’ self-assessment of digital communication and collaboration competencies and the motivation to train those. The results imply that the self-assessment of competencies and the motivation to train those cannot be influenced easily by varying instructions. Nevertheless, workers with high levels of digital communication and collaboration competencies also showed high motivation to train those. The findings of this dissertation provide a solid base for further theory building and extension in research on digital competencies at work. The insights gained from the studies of this dissertation comprise theoretical and practical implications for training development and human resource management. Overall, the results of this dissertation imply that digital competencies at work could be an important benefit in meeting the challenges of today’s digital work environments. The concept of digital competencies at work deserves more attention in future research.